Cost Comparison and Performance of Different Types of Reinforcement for Two –Way Slabs - Muhamed, Ahmed Heidayet (Sulaimani Journal for Pure and Applied Sciences, 2002)
The effectiveness of the member should not take only from strength point of view, but also from other considerations. A cost analysis of two-way concrete slabs was studied. The variables were type of reinforcement (bars,fibers, and wire meshes),and cost of materials (including cost of labors). The results indicated that the variation of steel content and labor prices seems to have a significant contribution in the cost objective function. Cost of ferrocemnt slab panels is high relative to its performance, while fibrous slab panels have more ductility with less cost.
Keywords: slabs; cost; ferrocement; steel finer; twoway slab; labor cost; ductility; reinforced concrete